1998
DOI: 10.1080/01635589809514677
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of subcutaneously transplanted hepatomas without cachexia by alteration of the dietary arginine‐methionine balance

Abstract: Previous studies have shown that alteration of the dietary arginine-methionine balance by use of synthetic L-amino acids inhibits tumor growth of a subcutaneously transplanted Morris hepatoma at the expense of maintaining body weight. However, L-methionine is susceptible to degradation and, therefore, may contribute to a deficiency state. The present studies were performed to determine whether growth of subcutaneous hepatoma transplants is inhibited, and body growth maintained, when rats are fed diets containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…29 The stimulatory effect of TPN on tumor growth parameters is recognized in rodent research, and recent work has focused on manipulating specific dietary components to counteract this phenomenon. [30][31][32] Ye et al, 30 Millis et al, 31 and He et al 32 have all independently compared various nutrition formulations and found that manipulation of specific amino acid concentrations-focusing on arginine and methionine balance-inhibited tumor growth in tumor-bearing rodents. Interestingly, controversy exists in the literature as to whether TPN stimulates tumor growth in the animal model to a greater degree than oral dietary intake.…”
Section: Discussionmentioning
confidence: 97%
“…29 The stimulatory effect of TPN on tumor growth parameters is recognized in rodent research, and recent work has focused on manipulating specific dietary components to counteract this phenomenon. [30][31][32] Ye et al, 30 Millis et al, 31 and He et al 32 have all independently compared various nutrition formulations and found that manipulation of specific amino acid concentrations-focusing on arginine and methionine balance-inhibited tumor growth in tumor-bearing rodents. Interestingly, controversy exists in the literature as to whether TPN stimulates tumor growth in the animal model to a greater degree than oral dietary intake.…”
Section: Discussionmentioning
confidence: 97%
“…To date, a number of nutrients and micronutrients with anticancer properties have been identified in soybean, including isoflavones, phytosterols, inositol hexaphosphate, saponins, protease inhibitors, and bioactive peptides [2][3][4][5][6][7][8]. The anticancer properties of soybean may also be due to its amino acid balance, since it has low methionine and high arginine content; both conditions are known to inhibit tumour development [9][10][11][12]. Moreover, different amino acids have antioxidant capacity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary methionine restriction causes regression of a variety of animal tumors and inhibits metastasis in animal models [12,17,19 -22]. For example, altering the dietary arginine-methionine balance inhibited tumor growth without causing cachexia in rats with subcutaneously transplanted Morris hepatoma [21,22]. Also, substituting homocysteine for methionine reduced tumor growth and metastasis in a rat rhabdomyosarcoma cell line [12,17].…”
Section: Tumor Growth Inhibitory Effects Of Methionine Restrictionmentioning
confidence: 99%